2020
DOI: 10.21632/irjbs.13.3.307-315
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information and Communication Industry (ICT) in the Reduction of Greenhouse Gas Emissions in Canada

Abstract: According to the concerted efforts to reduce global greenhouse gas emissions (GHGE), the Information and Communication Industry (ICT) has received little attention as a significant contributor to GHG. ICT has a very significant role to play in reducing greenhouse gas emissions in Canada. While climate challenges increase, there is a growing need to reduce Greenhouse gas emissions. The ICT sector has an important role in enabling significant reductions in those emissions and costs. This current study aims to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Promoting their restoration could help with more than a third of the total carbon reduction needed by 2030 to achieve the goals of the Paris Agreement [26]. However, despite the benefits of forests and trees, deforestation and desertification continue at a high rate due to human activities and climate change, endangering millions of people [27].Similarly, several studies demonstrate that ICT has been recognized to combat climate change [28][29][30] by revealing changing climate signals, analyzing, and modeling climate change; and implementing mitigation and adaptation measures to improve human resilience. Cutting-edge ICT innovations have been identified as practical means of combating climate change [29,31,32].…”
Section: Relationships Between and Among CC Sfm And Ictmentioning
confidence: 99%
“…Promoting their restoration could help with more than a third of the total carbon reduction needed by 2030 to achieve the goals of the Paris Agreement [26]. However, despite the benefits of forests and trees, deforestation and desertification continue at a high rate due to human activities and climate change, endangering millions of people [27].Similarly, several studies demonstrate that ICT has been recognized to combat climate change [28][29][30] by revealing changing climate signals, analyzing, and modeling climate change; and implementing mitigation and adaptation measures to improve human resilience. Cutting-edge ICT innovations have been identified as practical means of combating climate change [29,31,32].…”
Section: Relationships Between and Among CC Sfm And Ictmentioning
confidence: 99%
“…Information and Communication Technology (ICT) enables global sustainability by offering innovative solutions for environmental monitoring, resource management, and sustainable practices, accelerating progress in areas such as education, healthcare, and economic opportunities [19][20][21][22][23][24][25]. The natural relationship between CC and forests, and the potential of ICT to prevent climate change and enhance SFM, emphasizes the interconnectedness of these domains in achieving global sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the PON is being deployed globally and due to these massive deployments, its power consumption contribution in the information and communication (ICT) sector has been increasing. For example from the year 2010 to 2015, the total power requirement of the ICT sector was around 20GW that is now expected to reach to 1.5 TW by 2025 2 which has been estimated to contribute to 14 percent of the global GHG emissions by 2040 6 …”
Section: Introductionmentioning
confidence: 99%
“…For example from the year 2010 to 2015, the total power requirement of the ICT sector was around 20GW that is now expected to reach to 1.5 TW by 2025 2 which has been estimated to contribute to 14 percent of the global GHG emissions by 2040. 6 Generally, PON is considered to be a green technology compared to both copper access network as well as the active optical network (AON) technology, however, it is always-ON requirement of optical network unit (ONU) due to the synchronous nature provides a research opportunity to reduce its power consumption. It has been reported that the use of energy conservations schemes is helping to reduce its carbon footprint.…”
mentioning
confidence: 99%